2013
DOI: 10.1111/liv.12133
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin inhibitors in liver transplantation – still champions or threatened by serious competitors?

Abstract: Current strategies for immunosuppression in liver transplant (LT) recipients include the design of protocols targeting a more individualized approach to reduce risk factors such as renal failure, cardiovascular complications and malignancies. Renal injury in LT recipients may be often multifactorial and is associated with increased risk of post-transplant morbidity and mortality. The quest for low toxicity immunosuppressive regimens has been challenging and resulted in CNI minimization protocols or CNI withdra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 47 publications
0
20
1
3
Order By: Relevance
“…Cyclosporine A and FK506 are both CNIs with similar mechanisms of action . Studies have confirmed the toxic effect of CNIs on β ‐cells, as these agents can lead to β ‐cell apoptosis or dysfunction.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Cyclosporine A and FK506 are both CNIs with similar mechanisms of action . Studies have confirmed the toxic effect of CNIs on β ‐cells, as these agents can lead to β ‐cell apoptosis or dysfunction.…”
Section: Discussionmentioning
confidence: 96%
“…Cyclosporine A and FK506 are both CNIs with similar mechanisms of action. 48,49 Studies have confirmed the toxic effect of CNIs on β-cells, [50][51][52] as these agents can lead to β-cell apoptosis or dysfunction. It has been reported that MMF and RAP do not cause diabetes and that RAP administered for the treatment of AR after liver transplantation can relieve insulin dependence.…”
Section: Risk Factors For Nodatmentioning
confidence: 94%
“…Mycophenolate mofetil is an antiproliferative immunosuppressant. It is a prodrug and is metabolized to mycophenolic acid in its active form (Franklin & Morris, 1994;Wang et al, 2013;Dall'Era, 2011;Aliabadi et al, 2012;Beckebaum et al, 2013). It is in the same class as azathioprine, though more selective in action and is often used as a steroid-sparing agent, particularly in autoimmune diseases and transplantation medicine to prevent graft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…This "steroidfree" strategy may be especially beneficial for patients with hepatitis C patients and for those with diabetes and hypertension. Antibody induction along with delayed CNI introduction can be used to preserve renal function in LT recipients and reduce renal dysfunction in those with impairment [24] . Overall, no significant increase in adverse side effects was observed in solid transplant recipients receiving antibody induction [23,25] .…”
Section: Antibodiesmentioning
confidence: 99%